Prenatal maternal cortisol concentrations predict neurodevelopment in middle childhood. (January 2017) - Davis, Elysia Poggi; Head, Kevin; Buss, Claudia; Sandman, Curt A.
Highlights: Cortisol plays a central role in regulation of fetal brain development. Fetal exposure to optimal levels of maternal cortisol may benefit neurodevelopment. Higher maternal cortisol late in gestation predicts child cortical thickness. Higher maternal cortisol is associated with better cognitive performance. Abstract: Glucocorticoids (cortisol in humans) are the end product of the hypothalamic-pituitary-adrenocortical (HPA) axis and are proposed as a key mechanism for programming fetal brain development. The present prospective longitudinal study evaluates the association between prenatal maternal cortisol concentrations and child neurodevelopment. Participants included a low risk sample of 91 mother-child pairs. Prenatal maternal plasma cortisol concentrations were measured at 19 and 31 gestational weeks. Brain development and cognitive functioning were assessed when children were 6–9 years of age. Structural magnetic resonance imaging scans were acquired and cortical thickness was determined. Child cognitive functioning was evaluated using standardized measures (Wechsler Intelligence Scale for Children IV and Expressive Vocabulary Test, Second Edition). Higher maternal cortisol concentrations during the third trimester were associated with greater child cortical thickness primarily in frontal regions. No significant associations were observed between prenatal maternal cortisol concentrations and child cortical thinning. Elevated third trimester maternal cortisol additionally was associated with enhanced child cognitive performance. Findings in this normative sample of typically developing children suggest that elevated maternal cortisol during late gestation exert lasting benefits for brain development and cognitive functioning 6–9 years later. The benefits of fetal exposure to higher maternal cortisol during the third trimester for child neurodevelopment are consistent with the role cortisol plays in maturation of the human fetus. It is plausible that more extreme elevations in maternal cortisol concentrations late in gestation, as well as exposure to pharmacological levels of synthetic glucocorticoids, may have neurotoxic effects on the developing fetal brain.